Leporinus britskii: a new anostomid species from the Tapajós and Jari drainages, Brazil (Characiformes: Anostomidae) - Da S. Feitosa, Francimário; Santos, Geraldo M. Dos; Birindelli, José L. O. (Zootaxa, 2011)
A new species of the genus Leporinus Agassiz, 1829 (Characiformes, Anostomidae) is described. The new species is similar to Leporinus amblyrhynchus, L. taeniatus, L. taeniofasciatus, L geminis, L. unitaeniatus, L. vanzoi, by having a dark longitudinal midlateral stripe and dark transversal bars on dorsum. However, the new species is distinguished from Leporinus amblyrhynchus by having four teeth on dentary (vs. three); from L. taeniatus by having 12 circumpeduncular scale series (vs. 16) and 37 to 39 scales on lateral line (vs. 36 to 37); from L. taeniofasciatus by having 12 circumpeduncular scale series (vs. 16); from L. geminis, L. unitaeniatus and L. vanzoi by having three teeth on premaxilla (vs. four), 37 to 39 scales on lateral line (vs. 40 to 43), four or five scale series above lateral line (vs. six), and 12 circumpeduncular scale series (vs. 16). The new species is distributed in the rio Teles Pires and rio Jamanxim, rio Tapajós basin, and rio Jari, clearwater tributaries of the lower portion of the Brazilian Amazon.